Hand Hygiene and Cross Infection Control among Dental Auxiliaries working in Private and Public Dental Institutes of Punjab - Hammad Hassan, Farwa Zahid, Muhammad Imran Ameer Malik, Asma Shakoor, Zenab Yaasir, Muhammad Zeeshan, (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To evaluate the knowledge attitude and practices of dental assistants regarding hand hygiene and cross infection control in public and private dental institutes. Methods: Survey was carried out on 240 subjects working in five private and two public dental institutes using online questionnaires developed by the authors, and distributed via E-mail and WhatsApp. The target population were dental assistants and hygienists. Survey included a confidentiality and consent statement. Data was analyzed using the IBM SPSS version 20. Results: There were 240 respondents and majority were male. 71.3% of the participants received formal training in hand hygiene. 51.7% were aware of the presence of cross infection manual at workplace, however, fewer were aware of it contents. There was a significant difference between auxiliaries of private and public dental institutes when it comes to wearing gloves without washing hands, usage of alcohol rub and following recommended steps of hand washing. The auxiliaries of public institutes were performing hand washing before touching the patients only. Majority of the respondents especially from public institutes (38.3%) believe that hand should be dried using paper towel. Conclusion: Auxiliaries of private institutes were more aware about hand hygiene. Public institutes’ auxiliaries were lacking in knowledge and practice especially when it comes to usage of alcohol-based rub, washing hands before wearing gloves and performing hand hygiene before and after touching the patients. Regular workshop and courses should be done to keep their adherence to quality hand hygiene especially in public institutes. Keywords: American Dental Association, Center for Disease Control, Cross Infection, Dental Assistants, Hand Hygiene, Hygienists, World Health Organization